Neural Approaches to Conversational AI - Tutorial at ACL/SIGIR 2018 - Gao, Jianfeng; Galley, Michel; Li, Lihong (ACL and SIGIR tutorial, 2018)
This tutorial surveys neural approaches to conversational AI that were developed in the last few years. We group conversational systems into three categories: (1) question answering agents, (2) task-oriented dialogue agents, and (3) social bots. For each category, we present a review of state-of-the-art neural approaches, draw the connection between neural approaches and traditional symbolic approaches, and discuss the progress we have made and challenges we are facing, using specific systems and models as case studies.
ACL and SIGIR tutorial